2021
DOI: 10.2147/cmar.s285002
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of the Shouzu Ning Decoction Treatment for Multi-Kinase Inhibitors-Associated Severe Hand–Foot Skin Reaction

Abstract: Background: Multi-kinase inhibitors (MKIs) treatment plays an important role in cancer therapy, but still suffers from a high incidence of hand-foot skin reaction (HFSR), leading to MKIs dose modification or termination. Thus, there is a high need for therapeutic strategy for HFSR. Patients and Methods: This prospective analysis included twenty patients, who were continuously administered with MKIs treatment and presented with a grade 3 HFSR during January 2018 to December 2019. All the patients were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The median PFS achieved with these drugs ranged from 5.4 to 11.7 months, suggesting their potential in managing RAI-RDTC [79][80][81][82][83][84]. Overall, these findings highlight the remarkable progress of TKItargeted therapy in patients with dedifferenti-Am J Cancer Res 2024;14(2):407-428 found to relieve symptoms of HFSR according to a study [95]. However, it is important to note that the prevention and treatment of adverse events using TCM require more stringent trials and accurate evaluation criteria to verify their efficacy.…”
Section: Molecular Targeted Therapy In Advanced Thyroid Carcinomamentioning
confidence: 75%
“…The median PFS achieved with these drugs ranged from 5.4 to 11.7 months, suggesting their potential in managing RAI-RDTC [79][80][81][82][83][84]. Overall, these findings highlight the remarkable progress of TKItargeted therapy in patients with dedifferenti-Am J Cancer Res 2024;14(2):407-428 found to relieve symptoms of HFSR according to a study [95]. However, it is important to note that the prevention and treatment of adverse events using TCM require more stringent trials and accurate evaluation criteria to verify their efficacy.…”
Section: Molecular Targeted Therapy In Advanced Thyroid Carcinomamentioning
confidence: 75%
“…The present study indicated that topical SND treatment for 4 weeks revealed a remission rate of 56.52%, which was significantly superior to that achieved by Halometasone plus Celecoxib treatment. 23 Furthermore, patients with SND treatment had better-alleviated symptoms of HFSR and better-improved quality of life compared to that in the Hal/Cxb group. In addition, the time to HFSR degradation was similar in both groups (10.46 days vs 13.17 days), indicating that a 2-week treatment is likely needed to be efficacious.…”
Section: Discussionmentioning
confidence: 89%
“…And the detailed fabrication process of the SND was shown in our previous study. 23 Halometasone cream and Celecoxib capsules were purchased from Bright Future Pharmaceuticals Factory (Hongkong, China, LOT:6201340) and Pfizer Pharmaceuticals LLC (Puerto Rico, America, LOT:DX7406), respectively. The main ingredient of halometasone cream is halometasone-hydrate, and its specification is 1 g: 0.5 mg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations